KERAGAAN PERTUMBUHAN DAN WARNA IKAN WILD BETTA (Betta sp.) DENGAN REKAYASA INTENSITAS CAHAYA DAN WARNA LATAR - Riani Rahmawati; Sawung Cindelaras; Eni Kusrini (Jurnal Riset Akuakultur, 2016)
Penelitian ini dilakukan untuk menguji pengaruh kondisi lingkungan dengan intensitas cahaya dan warna latar yang berbeda terhadap pertumbuhan dan warna ikan cupang (Betta sp.). Biota uji diberi kombinasi perlakuan perbedaan kondisi cahaya dan warna latar, yaitu: (A-1) 100 lux dan latar putih; (A-2) 100 lux dan latar hitam; (A-3) 100 lux dan latar biru; (B-1) 800 lux dan latar putih; (B-2) 800 lux dan latar hitam; (B-3) 800 lux dan latar biru; (C-1) 1.500 lux dan latar putih; (C-2) 1.500 lux dan latar hitam; dan (C-3) 1.500 Lux dan latar biru. Setiap perlakuan diulang tiga kali. Ikan diberikan pakan berupa larva Chironomus sp. secara ad libitum. Penelitian dilakukan selama 84 hari. Hasil terbaik diperoleh pada perlakuan A-1 (intensitas 100 lux dan latar putih), dengan laju pertumbuhan spesifik panjang dan bobot masing-masing sebesar 0,48 ± 0,06%/hari dan 0,75 ± 0,22%/hari; sintasan sebesar 100%, serta persentase perubahan hue (H), saturation (S), dan brightness (B) berturut-turut adalah 21 ± 18, 6 ± 10, dan 6 ± 18.This research was conducted to determine the effect of rearing environment and light intensity with different background coloration to improve the color quality and growth of wild betta fish (Betta sp.). The fishs which were placed in the small tanks and treated with different light intensities and background coloration. The treatments combinations were: (A-1) 100 lux and white background, (A-2) 100 lux and black background, (A-3) 100 lux and blue background, (B-1) 800 lux and white background, (B-2) 800 lux and black background, (B-3) 800 lux and black background, (C-1) 1,500 lux and white background, (C-2) 1,500 lux and black background, and (C-3) 1,500 lux and blue background. Each treatment was repeated three times. The fish were fed onfrozen Chironomus larvae twice a day. The research was conducted for 84 days. The result showed that the combination of 100 lux and white background resulted the best growth rate (0.48 ± 0.06 cm/day in length and 0.75 ± 0.22%/day in weight) and survival rate of 100%. The best combination had the value of hue (21 ± 18), saturation (6 ± 10), and brightness (6 ± 18).